Envolvimento das proteínas quinases ativadas por mitógeno e do fator de transcrição nuclear Kappa B em modelos experimentais de dor muscular inflamatória e pós-operatória - Lima, Flávia Oliveira de (2011)
Chronic pain is often associated with transcriptional and functional changes in neural systems involved in the transmission and modulation of nociceptive information. The transcription of several proteins involved in chronic pain is regulated by the transcription factor B (NFB). Furthermore, NFB is an important target of MAPKs (Mitogen-Activated Protein Kinase). Therefore, it was investigated the involvement of MAPKs (p38, ERK and JNK) and NFκB in two experimental models of persistent pain: inflammatory muscle pain and postoperative pain models. Pre-treatment with inhibitors of NFκB and MAPKs (p38, ERK and JNK) reduced the acute muscle hypernociception, but not persistent hypernociception. In addition, pharmacological inhibition of NFκB or p38 MAPK but not ERK and JNK, reduced postoperative hypernociception. To investigate the mechanisms by which NFκB contributes to postoperative hypernociception, we analyzed the effect of PDTC, an NFκB inhibitor, on the production of inflammatory mediators and expression of sodium channels involved in nociceptive sensitization. The incision elevated the levels of TNF-α and PGE2 as well as increased the expression of sodium channels Nav 1.8 and 1.9 in sensory neurons, these effects being were neutralized by PDTC. These data suggest that the surgical incision activates the p38 MAPK/NFκB pathway, which increases the expression of TNF-α and PGE2, responsible for the up regulation of sodium channels Nav 1.8 and Nav 1.9 in sensory neuron resulting in neuronal hyperexcitability and postoperative hypernociception. These results provide new evidence on the distinct roles of NFκB and MAPKs in the development of acute and persistent pain, and indicate that NFκB may be an interesting pharmacological target for the treatment of postoperative pain.